The doors are open : selected addresses - Watanabe, Takeshi (Makati, Philippines : Office of Information, Asian Development Bank, 1967)
The book highlights the progress of Asian Development Bank in the development of member countries. It also reflects upon factors which have impeded the pace and scope of economic advancement in the past and how it would be overcome.
Includes bibliographical footnotes
usc 05/10/18
Loans
Keywords: Asian Development Bank; Economic policy; Banks and banking, International; Asia